Presenilin1 inhibits glioblastoma cell invasiveness via promoting Sortilin cleavage - Wei Yang (BMC, 2021)
Abstract Background Alzheimer’s disease (AD) and glioblastoma are the most common and devastating diseases in the neurology and neurosurgery departments, respectively. Our previous research reports that the AD-related protein Presenilin1 represses cell proliferation by inhibiting the Wnt/β-catenin pathway in glioblastoma. However, the function of Presenilin1 and the underlying mechanism need to be further investigated. Methods The correlations of two genes were conducted on the R2 microarray platform and CGGA. Wound healing, Transwell assays and glioblastoma transplantation were performed to detect invasion ability. Phalloidin staining was employed to show cell morphology. Proximity ligation assays and protein docking assays were employed to detect two protein locations. We also employed western blotting to detect protein expression. Results We found that Presenilin1 clearly repressed the migration, invasion and mesenchymal transition of glioblastoma cells. Intriguingly, we observed that the expression of Presenilin1 was positively correlated with Sortilin, which is identified as a pro-invasion molecule in glioma. Furthermore, Presenilin1 interacted with Sortilin at the transmembrane domain and repressed Sortilin expression by cleaving it in glioblastoma cells. First, we found that Sortilin introduced the function of Presenilin1 in phosphorylating β-catenin and repressing invasion in glioblastoma cells. Last, Presenilin1 stimulation sharply suppressed the invasion and mesenchymal transition of glioblastoma in mouse subcutaneous and intracranial transplantation models. Conclusions Our study reveals that Sortilin mediates the regulation of β-catenin by Presenilin1 and transduces the anti-invasive function of Presenilin1, which may provide novel therapeutic targets for glioblastoma treatment. Video Abstract